Gas well deliquification - Lea, James Fletcher
"Over the years, Gas Well Deliquification has become the professional's choice for recognizing and minimizing the detrimental effects of liquid loading problems in gas wells. Now in its second edition, this essential reference is expanded to provide managers with a comprehensive look into the methods of successful production automation as well as tools for the profitable use, production, and supervision of coalbed gases. Comprehensive in its coverage, this book presents the latest techniques, equipment and chemicals used in dewatering gas wells."--Jacket.